Grain Boundary Chemical Anchoring via Bidirectional Active Site Additive Enables Efficient and Stable Perovskite Solar Cells. Issue 20 (20th June 2022) - Wang, Gang; Wang, Wenqi; Bai, Le; Zhou, Qian; He, Dongmei; Liu, Baibai; Zhao, Pengjun; Tan, Lin; Li, Yuelong; Wei, Dong; Chen, Jiangzhao
Abstract: The nonradiative recombination induced by trap states at the surface and grain boundaries impedes the further increase of power conversion efficiency (PCE) and stability of perovskite solar cells (PSCs). Consequently, it is highly desirable to minimize the trap‐assisted nonradiative recombination in perovskite films. Here, an effective additive engineering strategy is reported where N‐succinimidyl 6‐maleimidohexanoate (denoted as NSMH) with multiple active sites and hydrophobic alkyl chains were incorporated for fully eliminating undercoordinated Pb 2+ traps in perovskite films. It is revealed that improved crystallinity and reduced defect density are achieved, which is ascribed to the strong coordination interaction between the carbonyl groups at both sides of NSMH molecules and Pb 2+ . As a result, the NSMH‐modified device exhibits a champion PCE of 22.40% with negligible hysteresis, which is significantly higher than 20.67% of the control device. The unencapsulated modified device exhibits no degradation while the control device degrades to 82% of its initial PCE after storing for 1536 h in a relative humidity of 10–20% at room temperature in the dark. Abstract : An effective additive engineering strategy is reported where N‐succinimidyl 6‐maleimidohexanoate (NSMH) with bidirectional active site and hydrophobic alkyl chains are introduced into perovskite precursor to eliminate undercoordinated Pb 2+ traps in perovskite films. The efficiency improves from 20.67% to 22.40% after NSMH modification along with improved stability.